LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK FUN GAME EFEKTIF MENGURANGI PERILAKU AGRESIF VERBAL PADA SISWA KELAS VIII SMP 40 SEMARANG TAHUN PELAJARAN 2012/2013 - Siwinarti, Siwinarti (Universitas Negeri Semarang, 2013)
The Efforts to Reduce the Students’ Aggressive Verbal Behavior through a Group Counseling by Using Fun Game Technique for 8 Grade of SMP 40, Semarang, Academic Year 2012/2013. The aggressive verbal behavior can be defined as a phenomenon of uncontrolled emotion behaving rude, having quirell, abusing, bullying and being high tempered. There is 16% of 156 students of the 8 th th grade students of SMP 40, Semarang indicates those behaviors. This research is aimed: to know the implementation of group counseling in the school and the decrease of the students’ aggressive verbal behavior, to know the effectiveness of group counseling model by using fun game technique to reduce the students’ aggressive verbal behavior. The method used in this research is action research, that is a research of action two cycles. The data analysis method that is used is descriptive analysis and t-test statistics and annova test. The sampling techinique is purposive sampling. The sample is the students behaving verbal aggressive, they are devided into high and middle based on the poll results questionnaire. The group counseling using fun game technique is effective in reducing the students aggressive verbal behavior after conducted within 2 cycles of action. Comparing to the former condition, the result of post test shows the decrease 28,29% is compared to aggressive verbal behavior.